Herbicidal activity and biochemical characteristics of the botanical drupacine against Amaranthus retroflexus L. - Hua-long YU; Ci TIAN; Rong-yan SHEN; Han Zhao; Juan YANG; Jin-gao DONG; Li-hui ZHANG; Shu-jie MA (Journal of Integrative Agriculture, 2023)
Botanical herbicide has been a hot topic in the research and development of novel pesticides. The herbicidal activity and biochemical characteristics of the botanical compound drupacine were studied by evaluating its effects on seed germination, seedling growth, morphological and physiological characteristics of Amaranthus retroflexus. Drupacine inhibited seed germination and seedling growth, and had a median inhibition concentration (IC50) value of 38.99 mg L−1 against A. retroflexus root. The α-amylase activity and soluble sugar content in treated plants were significantly lower than that of the control. The expression of α-amylase gene was dosage-dependently inhibited compared to the untreated control. This suggested that inhibition of α-amylase activity was a mode of action on seed germination. The root hairs were significantly decreased and part of the root cap fell off after treatment with drupacine. The ultrastructure observation showed that cell damage of root tips increased with the treatment time. Drupacine also increased the relative conductivity and malondialdehyde (MDA) content. Peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD) activities were significantly enhanced in the treatment compared to the control. These findings indicated that the physiological and biochemical reaction changes leading to morphological and membrane injuries were the main effects of drupacine on the inhibition of seedling growth. Drupacine can be developed as a botanical herbicide.